THE PRESENCE OF HEAVY METALS IN USED CLOTHES AND THEIR IMPACT ON HUMAN HEALTH - Odeh , Duha yousif Aziz; jead , Ahmed Radiy shimran jead; hasen, Mohammed taha sahb; Hassoun, Mohammed Taqi Abbas Abboud; Mohammed , Ahmed khuder abd Al Akhwa (Journal of Medical Genetics and Clinical Biology, 2024)
The research aims to detect the presence of heavy elements in used clothes and to educate people about their dangers and the diseases they carry in order to provide some solutions and recommendations for this problem. To achieve this goal, laboratory tests (atomic spectrometer) were conducted, which included 12 samples from different areas of Diwaniyah Governorate on 2/2/2021. The samples came in varying proportions. The percentage of arsenic increased in the intersection street by 30% and decreased in Alawi Street by 25%. As for the cadmium element, its concentration increased in Alawi Street by 20% and decreased in Alawi Street by 10%. As for lead, its percentage increased in the intersection street by 15% and decreased in Alawi Street by 10%. This difference is due to the presence of a fuel filling station behind the intersection street, so the percentage was greater. The quality of the clothes was estimated to be low, bad and dangerous to human health. Therefore, we recommend the necessity of carrying out sterilization operations and increasing monitoring of the places of their import and display to ensure the efficiency of the treatment and sterilization facilities